MIDDLE SCHOOL SCIENCE TEACHER RESPONSE TO ONLINE LEARNING DURING COVID 19 OUTBREAK - Rahmah Evita Putri; Monica Prima Sari; Rani Oktavia (Pendidikan IPA, FMIPA, UNP, 2020)
Afer 9 month doing online learning, a lot of things can happen in learning and teaching process. The purpose of this research is to know the respond of middle school science teacher to online learning during COVID 19 outbreak. This is a descriptive qualitative research with questionnaire as the research instrument. The sample are 35 middle school science teachers from MGMP IPA Kota Padang. The auestionnaire shows that most of the science teacher do an online learning through this year because of the COVID 19 Pandemis. Whatsaap is the most used application and online learning really helps the teacher with teaching. Furthermore, there are a lot of obstacle with online learning that science teacher faces during COVID 19 outbreak and most of the teachers hope that learning will continue face to face in the classroom.